Design and Fabrication of Noise Silencer for Grass Trimmer - Rajali, Azmir; JAMIAN, RAHIM (Progress in Engineering Application and Technology, 2021)
Grass trimming employees work in a noisy condition every day as they hold the grass trimming machine on their back. Over several years, this everyday exposure can lead to noise-induced hearing loss. In fact, reducing the noise emissions generated by the engine exhaust system poses a major problem for various industries. In this respect, mufflers have been used to reduce the emitted noise from the automobile engine into the environment. This research project was attempted to design and fabricate a noise silencer for grass trimmer. The scope was based on the existing grass trimming machine and the design of the muffler as a noise silencer for the grass trimmer. The design of a prototype model of the silencer was developed with the aid of SolidWorks software based on secondary data from the previous research study. The selection of the final design was founded on the advantages of the muffler that can be attached outside of the trimming engine. Then, the measurement of the noise level of the grass trimmer was conducted using a noise level meter. The equipment was set up at 0 – 10 m between the operator and engine with the operation condition of 1000 and 6000 rpm. Based on the measurement and analysis results, the noise level of the grass trimmer reduced significantly with a longer distance after applying the silencer for both the condition of 1000 and 6000 rpm. The overall findings suggested that the proposed prototype model of the silencer is effective to be used as an improvement opportunity to decrease the level of noise toward minimizing the harmful effect and risk of noise emitted by the engine of a grass trimmer. Nonetheless, several recommendations are highlighted for further development and improvement of the research, including redesigning the silencer to suit the characteristics of the commonly used grass trimmer.